2002
DOI: 10.1364/ol.27.002004
|View full text |Cite
|
Sign up to set email alerts
|

Blood analysis by Raman spectroscopy

Abstract: Concentrations of multiple analytes were simultaneously measured in whole blood with clinical accuracy, without sample processing, using near-infrared Raman spectroscopy. Spectra were acquired with an instrument employing nonimaging optics, designed using Monte Carlo simulations of the influence of light-scattering-absorbing blood cells on the excitation and emission of Raman light in turbid medium. Raman spectra were collected from whole blood drawn from 31 individuals. Quantitative predictions of glucose, ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 9 publications
6
133
0
2
Order By: Relevance
“…A subsequent whole blood study by Enejder et al 22 in our laboratory confirmed this hypothesis and they were able to demonstrate the feasibility of measuring multiple analytes in 31 whole blood samples with laser intensity and integration time similar to the previously mentioned serum study. 23 A 4X increase in Raman signal collection was achieved by employing a paraboloidal mirror and a shape-transforming fiber bundle for better collection efficiency, as depicted in Figure 5.…”
Section: Whole Bloodsupporting
confidence: 76%
See 1 more Smart Citation
“…A subsequent whole blood study by Enejder et al 22 in our laboratory confirmed this hypothesis and they were able to demonstrate the feasibility of measuring multiple analytes in 31 whole blood samples with laser intensity and integration time similar to the previously mentioned serum study. 23 A 4X increase in Raman signal collection was achieved by employing a paraboloidal mirror and a shape-transforming fiber bundle for better collection efficiency, as depicted in Figure 5.…”
Section: Whole Bloodsupporting
confidence: 76%
“…17 With the advent of high quantum efficiency CCD detectors and holographic diffractive optical elements, researchers have increasingly employed CCD-based dispersive spectrometers. 3,[18][19][20][21][22][23][24] The advantages of dispersive NIR Raman spectroscopy are that compact solid-state diode lasers can be used for excitation, the imaging spectrograph can be f-number matched with optical fibers for better throughput, and cooled CCD detectors offer shot-noise limited detection.…”
Section: Instrumentationmentioning
confidence: 99%
“…The Raman spectroscopy is powerful and versatile technique that enables investigation of molecular composition of human tissues, including measurement of blood parameters [4,8,9]. This method is based on the recording and analysis of light scattered inelastically by the investigated object.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…However, the influence of fluorescence induced by a laser beam, which is usually the strongest for the excitation wavelength range from 270 to 700 nm, must also be taken to account. Commonly used 830 nm laser [4,9], although is good solution when need of reduction of the fluorescence is considered, has also serious drawbacks. Respective Raman signal is generated in a spectral range where sensitivity of CCD arrays is poor as well as absorption of the radiation in water can be serious problem.…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation